1996
DOI: 10.1159/000244338
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Anticonvulsant Action of Baclofen Does Not Change during Development

Abstract: The possible anticonvulsant action of baclofen, a GABAb (γ-aminobutyric acid) receptor agonist, was studied using two types of motor seizures (minimal, clonic and generalized tonicoclonic) elicited by pentylenetetrazol in adult rats and rat pups, 7, 12, 18, and 25 days old. If baclofen was administered intraperitoneally (only in 12- and 25-day-old rats), no effect could be observed in 25-day-old animals. In 12-day-old rats, only the 12-mg/kg dose led to a prolongation of the generalized tonicoclonic seizure la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…If the activation of presynaptic GABA B receptors depresses GABA release, then the earlier appearance of presynaptic GABA B ‐receptor function would be expected to promote synaptic excitability. Although a clear role or age dependence of GABA B receptors in the generation or suppression of limbic seizures has not been established (85), GABA B ‐receptor activation in the thalamus is clearly required for the generation of absence seizures in most animal models, including those that mimic the age dependence of clinical absence epilepsy (83). Thus, it has been suggested that the age dependence of absence seizures may derive from a mismatch in the rates of maturation of GABA B ‐mediated and glutamate receptor–mediated transmission in thalamocortical circuits such that the maturation of NMDA‐receptor function lags behind that of GABA B receptors before adulthood (83).…”
Section: Maturational Factors That May Enhance Seizure Susceptibilitymentioning
confidence: 99%
“…If the activation of presynaptic GABA B receptors depresses GABA release, then the earlier appearance of presynaptic GABA B ‐receptor function would be expected to promote synaptic excitability. Although a clear role or age dependence of GABA B receptors in the generation or suppression of limbic seizures has not been established (85), GABA B ‐receptor activation in the thalamus is clearly required for the generation of absence seizures in most animal models, including those that mimic the age dependence of clinical absence epilepsy (83). Thus, it has been suggested that the age dependence of absence seizures may derive from a mismatch in the rates of maturation of GABA B ‐mediated and glutamate receptor–mediated transmission in thalamocortical circuits such that the maturation of NMDA‐receptor function lags behind that of GABA B receptors before adulthood (83).…”
Section: Maturational Factors That May Enhance Seizure Susceptibilitymentioning
confidence: 99%
“…In a kindling-induced rat model of epilepsy, it has been shown that stimulation of GABAergic neurotransmission through GABA B R agonist baclofen (BLF) had an anti-convulsant effect, while inhibition of GABAergic activity through GABA B R antagonist CGP35348 had a pro-convulsant effect in developing rats of 12 and 25 days ( Mares and Slamberová, 2006 ). Furthermore, BLF showed an anti-convulsant effect in pentylenetetrazol-induced model of epilepsy in developing rats of 7, 12, 18, and 25 days ( Kubová et al, 1996 ). In adult rats, BLF reduced pentylenetetrazol-induced seizures ( Chen et al, 2004 ) and electroshock-induced seizures ( Hyder Pottoo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%